The Growing Burden of Invasive Melanoma: Projections of Incidence Rates and Numbers of New Cases in Six Susceptible Populations through 2031 - Whiteman, David C; Green, Adele C; Olsen, Catherine M (Journal of investigative dermatology, 2016)
New melanoma therapies are being developed rapidly, complementing prevention and detection strategies for disease control. Estimating the future burden of melanoma is necessary for deciding how best to deploy limited resources to achieve effective melanoma control. Using three decades of cancer registry data (1982-2011) from six populations with moderate to high melanoma incidence (US whites and the populations of the United Kingdom, Sweden, Norway, Australia, New Zealand), we applied age-period-cohort models to describe current trends and project future incidence rates and numbers of melanomas out to 2031. Between 1982 and 2011, melanoma rates in US whites, and the populations of the United Kingdom, Sweden, and Norway increased at more than 3% annually and are projected to continue rising until at least 2022. Melanoma incidence in Australia has been declining since 2005 (-0.7% per year), and melanoma incidence in New Zealand is increasing but is projected to decline soon. The numbers of new melanoma cases will rise in all six populations because of aging populations and high age-specific rates in the elderly. In US whites, annual new cases will rise from around 70,000 in 2007-2011 to 116,000 in 2026-2031, with 79% of the increase attributable to rising age-specific rates and 21% to population growth and aging. The continued increases in case numbers in all six populations through 2031 will increase the challenges of melanoma control.